Characterization of Bacillus isolates of potato rhizosphere from andean soils of Peru and their potential PGPR characteristics - Calvo,Pamela (2010)
Bacillus spp. are well known rhizosphere residents of many crops and usually show plant growth promoting (PGP) activities that include biocontrol capacity against some phytopatogenic fungi. Potato crops in the Andean Highlands of Peru face many nutritional and phytophatogenic problems that have a significant impact on production. In this context is important to investigate the natural presence of these microorganisms in the potato rhizosphere and propose a selective screening to find promising PGP strains. In this study, sixty three Bacillus strains isolated from the rhizosphere of native potato varieties growing in the Andean highlands of Peru were screened for in vitro antagonism against Rhizoctonia solani and Fusarium solani. A high prevalence (68%) of antagonists against R. solani was found. Ninety one percent of those strains also inhibited the growth of F. solani. The antagonistic strains were also tested for other plant growth promotion activities. Eighty one percent produced some level of the auxin indole-3-acetic acid, and 58% solubilized tricalcium phosphate. Phylogenetic analysis revealed that the majority of the strains belonged to the B. amyloliquefaciens species, while strains Bac17M11, Bac20M1 and Bac20M2 may correspond to a putative new Bacillus species. The results suggested that the rhizosphere of native potatoes growing in their natural habitat in the Andes is a rich source of Bacillus fungal antagonists, which have a potential to be used in the future as PGP inoculants to improve potato crop.